Targeting sites of inflammation: intercellular adhesion molecule-1 as a target for novel inflammatory therapies - Hua, Susan (Frontiers in Pharmacology, 2013)
Targeted drug delivery to sites of inflammation will provide effective, precise and safe therapeutic interventions for treatment of diverse disease conditions, by limiting toxic side effects and/or increasing drug action. Disease-site targeting is believed to play a major role in the enhanced efficacy observed for a variety of drugs when formulated inside lipid vesicles. This article will focus on the factors and mechanisms involved in drug targeting to sites of inflammation and the importance of cell adhesion molecules, in particular ICAM-1, in this process.